1988
DOI: 10.1007/bf03350119
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin response to insulin-induced hypoglycemia in obese subjects before and after weight loss

Abstract: The response of plasma oxytocin to an iv bolus injection of crystalline insulin (0.15 U/kg) was evaluated in 14 normal weight [mean body mass index (BMI) = 23] and in 9 obese (mean BMI = 42) men. Similar blood glucose decrements after insulin injection were observed in the two groups. Obese and normal weight subjects presented similar basal oxytocin levels. In both groups, oxytocin rose significantly during the insulin tolerance test (ITT); however, the peak oxytocin response in the obese men was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…In this regard, we hypothesize that the high BMI values of our obese patients could have yielded a broad bulky effect on oxytocin secretion. To date, oxytocin levels in obesity have been found decreased [18], unchanged [41], or even increased [24] as compared to controls. Several reasons could contribute to explain these discrepancies, such as differences in study cohorts, gender prevalence, degree of obesity, sampling procedures, and analytical methodologies [21,28].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we hypothesize that the high BMI values of our obese patients could have yielded a broad bulky effect on oxytocin secretion. To date, oxytocin levels in obesity have been found decreased [18], unchanged [41], or even increased [24] as compared to controls. Several reasons could contribute to explain these discrepancies, such as differences in study cohorts, gender prevalence, degree of obesity, sampling procedures, and analytical methodologies [21,28].…”
Section: Discussionmentioning
confidence: 99%
“…The tubes were placed in an ice bath and centrifuged in the cold; the plasma was separated and stored at -2 0 °C until assayed. Plasma OT [15,16], ACTH [17] and cortisol [18] concentrations were measured with specific ra dioimmunoassay (R1A) methods. All samples from the same sub jects were measured in duplicate in the same assay.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma AVP [15] and OT [3,15] were measured by specific R1A methods, as previously described. The limits of detection of the AVP and OT assays were 1.2 and 2.0 pg/ml, respectively.…”
Section: Assaysmentioning
confidence: 99%
“…These data exclude a di rect role of hyperinsulinemia in the mechanism underlying the AVP and OT responses during ITT. Furthermore, since glucose, but not fructose, crosses the blood-brain barrier (BBB), the posterior pituitary hormone responses to hypoglycemia appear to be generated by stimulations of glucosensitive areas located inside the BBB.Insulin-induced hypoglycemia is a primary stimulus for the secretion of both posterior pituitary hormones ar ginine vasopressin (AVP) and oxytocin (OT) [1][2][3]. Even though a direct action of insulin at the hypothalamic level has been reported [4][5][6][7], normoglycemic hyperinsuliné mie clamp studies have demonstrated that hyperinsuline mia does not promote vasopressin secretion [8], There fore, the AVP and OT responses during an insulin toler ance test (ITT) are supposed to follow direct stimulation of hypothalamic glucoreceptors [4][5][6][7] elicited by the neuropenic symptomatic stimulus [9][10][11][12].…”
mentioning
confidence: 99%